Pengaruh Likuiditas, Struktur Kepemilikan, dan Return On Assets (Roa) Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur di Bursa Efek Indonesia (BEI) Tahun Periode 2015-2019 - Egi Prayana; Sunitha Devi (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
AbstrakThis study aims to examine the effect of Liquidity, Ownership Structure, ROA on Dividend Policy in manufacturing companies on the Indonesia Stock Exchange for the period 2015-2019. Using independent variables including liquidity, ownership structure, return on assets. Whereas the dependent variable used is Dividend Policy. Sample selection in research on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. The sample selection technique in this study uses purposive sampling, with certain criteria adjustments so that it gets a total of 31 companies. Data supporting this research were obtained from the official website of the Indonesia Stock Exchange with a period of 5 years. The analysis in this study, used multiple linear regression test with the help of IBM SPSS version 20 application. The results of this study states that liquidity, ownership structure, and return on assets have a significant positive partial effect on dividend policy, for investors who want to invest their capital in a Companies in the capital market should consider carefully in analyzing the company's performance in order to invest in getting dividends.